Can Auditors Pursue Firm-Level Goals Nonconsciously on Audits of Complex Estimates? An Examination of the Joint Effects of Tone at the Top and Management's Specialist - Pyzoha, Jonathan S.; Taylor, Mark H.; Wu, Yi-Jing (The Accounting Review, 2020)
ABSTRACT We examine whether tone at the top emphasizing firm-level commercial, audit quality, or both goals (balanced) can nonconsciously affect auditors' engagement-level tendency to accept management's estimates, and whether the effects differ if management engages a specialist. This study is motivated by academics' and regulators' increasing attention on firm-level tone at the top and concerns about management bias in audited estimates, especially when the evidence is prepared by management's specialist. We find firm-level goals can be pursued nonconsciously by auditors when performing a complex task. When management's specialist is absent, a balanced approach reduces auditors' tendency to agree with management's estimate compared to a commercial approach; however, it is less effective when management's specialist is present. We find an audit quality approach reduces auditors' tendency to accept management's estimate compared to a commercial approach, regardless of the absence/presence of a specialist. Our results have important implications for regulators and audit firms. Data Availability: Data are available from the authors upon request.